Q. 375.0( 1 Vote )

Prove that: <span

Answer :

Formula : -

(i) Cos 3 a = 4 cos3 a – 3 cos a

(ii) sin3a = 3sina – 4sin3a

(iii) a3 – b3 = (a2 – b2)(a2 + b2 + ab)

(iv) sin2a + cos2a = 1

Taking L.H.S we get,

using formula (i) and (ii)

taking common (cos a – sin a) and using formula (iii)

using formula(iv)

L.H.S = R.H.S

Hence, Proved.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses